1986
DOI: 10.1104/pp.82.1.136
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Carbon Flow by Nitrogen and Light in the Red Alga, Gelidium coulteri

Abstract: The red alga Gelidium coulteri Harv. photosynthetically fixed 11'4C bicarbonate at high rates under defined conditions in unialgal laboratory culture. The fixation rate and flow of photosynthate into various end products were dependent on the nitrogen status of the tissue. Plants fed luxury levels of nitrogen (approximately 340 micromolar) showed fixation rates several-fold higher than those seen for plants starved for nitrogen. algal species for both agar and the related polysaccharide, carrageenan (2,17). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
1
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 10 publications
5
68
1
1
Order By: Relevance
“…Carbon and nitrogen metabolism are related by a demonstrable inverse relationship between agar synthesis and carbon metabolism on one hand, and protein synthesis and nitrogen metabolism on the other (Hanisak, 1983), that has been shown indirectly for some species of Gelidium in culture (Macler, 1986(Macler, , 1988Fredriksen & Rueness, 1989, Torres et al, 1991. In addition, populations of red algae, including members of the Gelidiales, around the world show a characteristic summer 'bleaching', described as a loss of pigmentation related to environmental conditions (Neish et al, 1977;Santelices, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon and nitrogen metabolism are related by a demonstrable inverse relationship between agar synthesis and carbon metabolism on one hand, and protein synthesis and nitrogen metabolism on the other (Hanisak, 1983), that has been shown indirectly for some species of Gelidium in culture (Macler, 1986(Macler, , 1988Fredriksen & Rueness, 1989, Torres et al, 1991. In addition, populations of red algae, including members of the Gelidiales, around the world show a characteristic summer 'bleaching', described as a loss of pigmentation related to environmental conditions (Neish et al, 1977;Santelices, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…In red algae, research has concentrated on the economically important species of Gracilaria and Chondrus (DeBoer, 1978;Ryther et al, 1978;Rosenberg & Ramus, 1982;Bird et al, 1982;Bird, 1984;Friedlander & Dawes, 1985;Fujita, 1985;Dawes & Koch, 1990;Friedlander et al, 1990;Hanisak, 1990) and tank cultures of Palmaria palmata (Morgan & Simpson, 1981a, b) and Chondrus crispus (Neish et al, 1977). Information about metabolism in species of the economically important order Gelidiales is limited and confined to descriptions of seasonal changes in agar content (Establier, 1964;Garda, 1988;Mouradi-Givemaud et al, 1992), assimilation of ammonium and nitrate (Bird, 1976) and short-term pulse-chase experiments (Macler, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the hexose/ protein and hexose/Chl ratios in Nod+/+ were diminished by as much as 6 times less than the Nod+/-plants (Table II). This same trend has been demonstrated previously in a study of photosynthate partitioning in algae (20). Clearly, when inorganic nitrogen assimilation and N2 fixation concurrently exert a major control upon foliar photosynthate partitioning, as it does in soybean, then both the carbohydrate assimilates and the nitrogen assimilates must be examined before a complete understanding of control points can be elucidated.…”
Section: Maintenance Of Photosynthetic Rate In Nod+/-source Leaves Tomentioning
confidence: 86%
“…Nitrogen deficiency can bring about lower net photosynthetic rates in nonnodulated legumes and in other plants (5,28). Nitrogen limitations will bring about changes in carbohydrate to protein ratios in algae, with carbohydrate synthesis favored by low nitrogen availability while protein synthesis is favored by high nitrogen availability (20). Protein usually is not considered to be stored photosynthate.…”
mentioning
confidence: 99%
“…There have been reports showing that red algae accumulate sugar under nitrogen-depleted conditions (Macler, 1986;Razaghi et al, 2014); however, they were not focused on the relationship to TAG accumulation. We showed that the primitive red alga C. merolae accumulates not only TAG but also starch under nitrogen-depleted conditions.…”
Section: Neutral Lipid and Sugar Contents During Culturingmentioning
confidence: 99%